Mathematical Modelling of Convection Drying Characteristics of Artichoke (Cynara scolymus L.) Leaves - Abdülkadir Yağcıoğlu; Tuncay Günhan; Vedat Demir (Journal of Agricultural Sciences)
This paper presents the results of a study on mathematical modelling of convection drying of artichoke (Cynara scolymus L.) leaves. Artichoke leaves used for drying experiments were picked from the agricultural faculty experimentation fields on the campus area of Ege University. Chopped artichoke leaves were then used in the drying experiments performed in the laboratory at different air temperatures (40, 50, 60 and 70 °C) and airflow velocities (0.6, 0.9 and 1.2 m s) at constant relative humidity of 15±2%. Drying of artichoke leaves down to 10% wet based moisture content at air temperatures of 40, 50, 60 and 70 °C lasted about 4.08, 2.29, 1.32 and 0.98 h respectively at a constant drying air velocity of 0.6 m s while drying at an air velocity of 0.9 ms took about 3.83, 1.60, 0.96 and 0.75 h. Increasing the drying air velocity up to 1.2 m s at air temperatures of 40, 50, 60 and 70 °C reduced the drying time down to 3.5, 1.54, 1.04 and 0.71 h respectively. Different mathematical drying models published in the literature were used to compare based on the coefficient of multiple determination (R), root mean square error (RMSE), reduced chi-square (χ) and relative deviation modulus (P). From the study conducted, it was concluded that the Midilli et al drying model could satisfactorily explain convection drying of artichoke (Cynara scolymus L.) leaves under the conditions studied.